Generation of compensated ion beams from source with oscillating electrons - Borisko, V.N.; Petrushenya, A.A.; Yunakov, N.N. (Вопросы атомной науки и техники, 2000)
The generation of compensated ion beams from electrically unsymmetrical reflecting discharge was investigated. The spatial location of a compensation zone, the optimal values of operating gas pressures Ð = (0,8 ÷ 1)×10⁻⁴ Torr and potential difference between cathodes ΔU = 80Â were determined. The way to control the current compensation degree of the extracted ion beam from a several to 100% was found.